Reducing Aggression and Improving Physical Fitness in Adolescents Through an After-School Volleyball Program - Trajković, Nebojša; Pajek, Maja; Sporiš, Goran; Petrinović, Lidija; Bogataj, Špela (Frontiers in Psychology, 2020)
This study aimed to determine the effects of an after-school volleyball program on aggression and physical fitness in 14-16 years old students. One hundred and seven participants were randomized to a small-sided volleyball (SSV) training group or a control group (CON). The SSV group completed eight months of small-sided volleyball training twice a week after school in addition to the regular physical education classes. Yo-Yo Intermittent Recovery Level 1 test (YYIRT1), medicine ball throw (MED), vertical jump (VJ), and Buss and Perry’s aggression questionnaire were evaluated before and after eight months of training. Results revealed a significant main effect of group x time interaction in total sample for physical aggression (F(1, 105) = 17.688; p < 0.001), verbal aggression (F(1, 105) = 4.973; p = 0.028), anger (F(1, 105) = 7.662; p = 0.007), medicine ball throw (F(1, 105) = 36.143; p < 0.001), and YYIRT1 (F(1, 105) = 12.508; p = 0.001). After-school small-sided volleyball for adolescents was accompanied by a significant decrease in aggression compared to physical education classes only. Additionally, adolescents from SSV group showed better results in physical fitness compared to the control group. Our findings significantly contribute to the understanding of possible mechanisms for reducing adolescents’ aggression, which include enjoyment, motivation, and self-control through sport intervention.